4-Aminopyrazolopyrimidine scaffold and its deformation in the design of tyrosine and serine/threonine kinase inhibitors in medicinal chemistry. Issue 9 (29th July 2022) - Chen, Xiaolu; Huang, Yajiao; Xu, Wanghan; Cai, Yuepiao; Yang, Yuanrong
Abstract : Deformation of the 4-aminopyrazolopyrimidine scaffold in designing small-molecule inhibitors. Abstract : The 4-Aminopyrazolopyrimidine scaffold has been an interesting pharmacophore since the disclosure of the intimate connection between small-molecule inhibitors and the treatment of diseases. Modification of the 4-aminopyrazolopyrimidine scaffold according to different targets, especially tyrosine kinase and serine/threonine kinase, has resulted in a variety of small-molecule inhibitors. Kinase inhibitors with 4-aminopyrazolopyrimidine derivatives as scaffolds have been widely applied in the treatment of diseases. In this article, we summarized the reports on 4-aminopyrazolopyrimidine as well as its deformation and the application of its derivatives in designing small-molecule inhibitors and the treatment of diseases.